ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN BURUH TANI BERGESER KE SEKTOR INDUSTRI SARUNG TENUN IKAT JAVA ATBM DI DESA BEJI, KECAMATAN TAMAN, KABUPATEN PEMALANG - Sari Kusumastuti; Siti Hamidah; Juarini Juarini (Jurnal Dinamika Sosial Ekonomi, 2005)
The intensity of nonagricultural activity in a rural increase. It seen from availability of woven cloth industry of Beji district of Taman sub-province Pemalang, so it make the people who work in the agicultunal sector going move into it. The Job assumed is good and get high salary is a big incent for them to move. This make farmer moving on woven cloth industry. Method research by using case study with determination of sampel use method of Proportional Random Sampling. Factors influencing decision of labour farmer shift to weave case industrial sector fasten to be used by method of Regresi Binary Logistic. Result of research indicate that factors influencing decision of labour farmer to weave case industrial sector fasten is wage rate and age.Keywords: decision of labour farmen, wage rate, age